A Close Relationship Between Networks of Interstitial Cells of Cajal and Gastrointestinal Transit In Vivo - Kishi, Kazuhisa; Kamizaki, Moe; Kaji, Noriyuki; Iino, Satoshi; Hori, Masatoshi (Frontiers in Pharmacology, 2020)
The interstitial cells of Cajal associated with the myenteric plexus (ICC-MP) are located in the same area where is the myenteric plexus. ICC-MP networks are linked to the generation of electrical pacemaker activity that causes spontaneous gastrointestinal (GI) contractions; however, its role in GI transit is not clear. The aim of this study was to comprehensively investigate the effect of ICC-MP disruption on GI transit in vivo using W/Wv mice, partially ICC-deficient model mice. In this study, we measured GI transit using a 13C-octanoic acid breath test, an orally administered dye and a bead expulsion assay. ICC were detected by immunohistochemical staining for c-Kit, a specific marker for ICC. Interestingly, we found that gastric emptying in W/Wv mice was normal. We also found that the ability of small intestinal and colonic transit was significantly reduced in W/Wv mice. Immunohistochemical staining using whole-mount muscularis samples revealed that c-Kit-positive ICC-MP networks were formed in wild-type mice. In contrast, ICC-MP networks in W/Wv mice were maintained only in the gastric antrum and were significantly reduced in the ileum and colon. No significant changes were observed in the nerve structures of the myenteric plexus in W/Wv mice. These findings suggest that ICC-MP contribute to GI transit as a powerful driving function in vivo.